Pengaruh Latihan Yoga terhadap Involusi Uterus pada Ibu Nifas - Miftakhul Mu’alimah; Dewi Kartikasari; Sunaningsih Sunaningsih; Yunita Puspita Sari Pakpahan (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2022)
The puerperium period is the period used to restore the obstetric organs as before pregnancy with approximately 6 weeks, and this puerperal period lasts normally until the uterus returns to its original shape. A common puerperal complication is post partum hemorrhage, which is caused by one of them because the involution process is not running well. Puerperal yoga is a form of effort to make the involution process run normally, which aims to facilitate the occurrence of the uterine involution process, strengthening the pelvic floor muscles postpartum. The purpose of this study was to determine the Effect of Yoga Practice on Uterine Involution in Puerperal Mothers in PMB Mrs." K'' Mojoroto Kediri City. This study was an experimental quasy and used a desaign posttest control design. The study's population was all post partum mothers who gave birth normally day 1 to day 14, with a sample count of 32 puerperal mothers. The sampling technique uses accidental sampling technique which will be carried out in March – May 2022. Statistical tests using independent T-Test tests. The results of the study found that there was an influence of yoga practice on uterine involution in puerperal mothers with a value of ρ 0.0005. Research recommendations that yoga practice can be used to help the normal continuity of the involution process and can help improve the blood circulation of post partum mothers.